PENGARUH BUDAYA ORGANISASI TERHADAP PERILAKU PEGAWAI DALAM MENINGKATKAN KINERJA PEGAWAI DINAS KEHUTANAN DAN PERKEBUNAN KABUPATEN SUMEDANG - Teddy Marliadi Nurwan (Journal Of Regional Public Administration (JRPA), 2016)
This study aimed to analyze the influence of organizational culture on employee behavior in improving employee performance at the Dinas Kehutanan dan Perkebunan Kabupaten Sumedang. The method of research is descriptive analysis. The study population were employees of the Dinas Kehutanan dan Perkebunan Kabupaten Sumedang as many as 115 people. Sampling by using cluster random sampling. Survey respondents as many as 53 people. Data collected by documentation study and field study through observation, interviews and questionnaires, as well as data analysis techniques using path analysis model (path analysis). The results showed that organizational culture and a positive significant effect on the behavior of employees in improving the performance of staff at the Dinas Kehutanan dan Perkebunan Kabupaten Sumedang, amounting to 74,04%. Meanwhile, outside the influence of organizational culture and employee behavior amounted to 25,96%, that other factors not examined.